Penentuan Formulasi Terbaik Pembuatan Sampo Kendaraan Berbahan Dasar Sisa Produk Sampo di Industri Sampo - Fauzi, Muhammad Rezal Alfian; Hasannah, Cintiya Septa; Perdani, Meka Saima; Prajati, Gita (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
This research aims to process remaining shampoo products originating from the sampo industry into vehicle shampoo so that it has sales value and also has good quality. Determining the formulation for making this vehicle shampoo uses the trial and error method. After that, the variation data obtained will be tested through a pH test, density test, viscosity test, foam power test and corrosivity test. The results obtained are that the remaining variation data for the 25 mL shampoo product is the most optimal data because it meets the requirements for pH, density, viscosity and foaming test results. The results obtained from the variation data to make the best formulation were 47% remaining shampoo, 8% LAS, 8% NaCl (0.5 N), 8% NaOH (0.1 N), 0.4% Essense (Bubble Gum). %, and Aquadest 30%. This formulation produces a pH value of 7.18. Meanwhile, the density is 1.0257 g/cm3. The viscosity of this composition is 2.999 Pa.s. The stability of the foam power is 66,7% and the corrosion resistance test results get a value of 0.145655 mm/year or in the "Good" category in terms of corrosion resistance.